1998
DOI: 10.4269/ajtmh.1998.58.800
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and susceptibility to antibiotics of Shigella species in stools of hospitalized children with bloody diarrhea in Pakistan.

Abstract: The aim of the present investigation was to study the frequency of Shigella spp. in patients with bloody diarrhea in Pakistan and the susceptibility of isolated Shigella to three antibiotics: ampicillin, cotrimoxazole and nalidixic acid. In addition, the frequency of Campylobacter and Salmonella was also determined. Stool samples (n ϭ 152) were collected from 152 diarrheic children less than six years of age passing blood and mucus in their stools who were admitted to Paediatric Department of Mayo Hospital in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
2
17
1
Order By: Relevance
“…The studies found that from between 3% and 19% of stool specimens were Shigella positive [22][23][24]26,44]. In hospital based found studies Campylobacter was isolated from 17% to 25% of stool specimens [41,42,[46][47][48].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The studies found that from between 3% and 19% of stool specimens were Shigella positive [22][23][24]26,44]. In hospital based found studies Campylobacter was isolated from 17% to 25% of stool specimens [41,42,[46][47][48].…”
Section: Discussionmentioning
confidence: 98%
“…Our study is the foremost community based study to estimate the factual incidence of shigellosis on a population level. Earlier hospital based studies do not provide a denominator essential for incidence estimates [22][23][24][25][26][27][28][29]. Not only is it significant to appreciate the shigellosis incidence in a study area it is evenly imperative to understand the distribution of Shigella serogroups, types, and subtypes because the knowledge about cross protection between Shigella serotypes and subtypes is very limited at best [30].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to multiple antibiotics has been well documented in waterborne pathogens (106)(107)(108)(109) and represents a major public health threat. There are many pathways for antibiotics and antibiotic-resistant organisms to enter the drinking water supply (110,111).…”
Section: Emerging and Resurging Pathogensmentioning
confidence: 99%
“…are fragile organisms that are excreted in large numbers in the stool, but they die off quickly because stools are acidic [15]. Thus, routine microbiological methods used to identify Shigella spp.…”
Section: Introductionmentioning
confidence: 99%